Analisis Antaseden Reverse Logistics Capabilities Dan Penghematan Biaya Usaha Kecil Dan Menengah Di Surabaya Dan Sekitarnya - Febriana Wurjaningrum; Tuwanku Aria Auliandri (Universitas Airlangga, 2015)
This research is aimed to determine the relation of customer orientation, customer opportunism, resource commitment, contractual agreements, and reverse logistic capabilities as well as the relation of reverse logistic capabilities and reverse logistics cost savings. A statistical analysis method focused on testing hypotheses, path analysis, is used as the method of this research. Samples taken in this research involve both small and medium business enterprises (SMEs) in the areas of retail, manufacturing, handicrafts, and drug sellers (drug stores and pharmacies) located in Surabaya, Malang, Singaraja, and Denpasar. Those respondents, moreover, are directly involved in reverse logistics process as well as interacting with suppliers. The results of this research then show that there is a positive relation between customer orientation and reverse logistic capabilities. It is also known that there is a negative relation between customer opportunism and reverse logistic capabilities although the relation is less significant. Furthermore, there is also a positive relation between resource commitment and reverse logistic capabilities. There is also a positive relation between contractual agreements and reverse logistic capabilities although it is not significant. And, it is also shown that there is a positive relation between reverse logistic capabilities and cost savings. Thus, it may be concluded that all five hypotheses proposed in this research have indeed been proven empirically although there are a few variables showing less significant relations, which means that these variables less affect or impact on reverse logistic capabilities and ultimately on cost savings.